The meaning of postpartum sexual health for women living in Spain: a phenomenological inquiry - Lidia Pardell-Dominguez; Patrick A. Palmieri; Karen A. Dominguez-Cancino; Doriam E. Camacho-Rodriguez; Joan E. Edwards; Jean Watson; Juan M. Leyva-Moral (BMC, 2021)
Abstract Background Sexual health is a multidimensional phenomenon constructed by personal, social, and cultural factors but continues to be studied with a biomedical approach. During the postpartum period, a woman transitions to mother, as well as partner-to-parent and couple-to-family. There are new realities in life in the postpartum period, including household changes and new responsibilities that can impact the quality of sexual health. This phenomenon is understudied especially in the context of Spain. The purpose of this study was to describe the lived experience of postpartum sexual health among primiparous women giving birth in Catalonia (Spain). Methods This was a phenomenological study with a purposive sample of primiparous women. Data was collected through semi-structured interviews until saturation. Analysis followed Colaizzi's seven-step process with an eighth translation step added to limit cross-cultural threats to validity. Also, the four dimensions of trustworthiness were established through strategies and techniques during data collection and analysis. Results Ten women were interviewed from which five themes emerged, including: Not feeling ready, inhibiting factors, new reality at home, socio-cultural factors, and the clinician within the health system. Returning to sexual health led women to engage in experiential learning through trial and error. Most participants reported reduced libido, experienced altered body image, and recounted resumption of sexual activity before feeling ready. A common finding was fatigue and feeling overloaded by the demands of the newborn. Partner support was described as essential to returning to a meaningful relationship. Discussions about postpartum sexual health with clinicians were described as taboo, and largely absent from the care model. Conclusion Evidence-based practices should incorporate the best evidence from research, consider the postpartum sexual health experiences and preferences of the woman, and use clinician expertise in discussions that include the topic of postpartum sexual health to make decisions. As such, human caring practices should be incorporated into clinical guidelines to recognize the preferences of women. Clinicians need to be authentically present, engage in active communication, and individualize their care. More qualitative studies are needed to understand postpartum sexual health in different contexts, cultures, and countries and to identify similarities and differences through meta-synthesis.